Patentlizenzverträge im japanischen Antimonopolgesetz - Siegfanz, Frank (Zeitschrift für Japanisches Recht, 2004)
The regulation of patent licence agreements by competition law occurs at an interface where two apparently contradictory areas of law clash. The traditional “solution“ to this problem is to reduce the use of patents to the nucleus of what is necessary in terms of patent law. Under Art. 21 of the Japanese Antimonopoly Act (AMA), the execution of rights under the Patent Act is excluded from the application of the Antimonopoly Act. Under the guidelines issued in 1968, 1989 and 1999, the Japanese Fair Trade Commis-sion, which regulates patent licence agreements, is not impinging on the AMA. The guide-line of 1968 is closely based on § 20 GWB (old edition) and must be considered in the light of technological progress in Japan. The 1989 and 1999 guidelines are founded on the theory of reciprocal completion of patent law and the AMA. This theory has flaws in its reasoning. Article 21 of the AMA may be interpreted by referring back to the German Cartel Dissolution Laws. The law-makers understood patents as being legal monopolies. Control of internal growth based on patents through the AMA is therefore not possible.